A Retrospective, Unicentric Evaluation of Complicated Diverticulosis Jejuni: Symptoms, Treatment, and Postoperative Course - Téoule, Patrick; Birgin, Emrullah; Zaltenbach, Benjamin; Kähler, Georg; Wilhelm, Torsten J.; Kienle, Peter; Rückert, Felix (Frontiers in Surgery, 2015)
Background In contrast to the diverticulosis of the colon jejunal diverticulosis is a rare condition. The incidence is 0.06% up to 5% in large autopsy series. Complicated diverticulosis jejuni (CDJ) often presents with unspecific symptoms. Therefore diagnosis is often a challenging diagnosis and due to the clinical rarity no generally valid recommendation of perioperative management exists. Patients and Methods We considered only patients that were operated in our centre between April 2007 and August 2014. Patients were identified by data bank search via International Statistical Classification of Diseases and Related Health Problems (ICD) diagnosis code K57.10. Data was manually screened and patients with Meckel’s and duodenal diverticula were excluded from this study. Eleven consecutive patients with CDJ were finally included in this study. We analysed symptoms, diagnostic procedures, surgical treatment and postoperative morbidity and mortality. Results The median age of our patients was 76 years (range 34 87). CDJ presented most frequently as intestinal bleeding or as diverticulitis. Clinical symptoms were unspecific abdominal pain, hematemesis or melena, ileus, nausea and emesis as well as patients with acute abdomen. Esophagogastroduodenoscopies confirmed CDJ in two of three patients. An abdominal CT-scan only helped to diagnose CDJ in two of ten patients. Eight (72.7%) patients received an open segmental resection with primary anastomosis. In three (27.3%) cases a reoperation was necessary. Overall morbidity rate was 45.5% and perioperative mortality was 9.1%. Conclusions Due to the acute character of the disease patients with CDJ are seriously ill. To diagnose patients with CDJ remains challenging as diagnostic investigations are usually not helpful in confirming diagnosis. Still, diagnosis of CDJ is most frequently confirmed intraoperatively. Keywords: complicated jejunal diverticulitis, perioperative management, acute abdomen, visceral surgery, rare disease